Antimicrobial Formulation of Chrysopogon zizanioides Essential Oil in an Emulsified Lotion for Acne - Kurrimboccus, Fadilah; Orchard, Ané; Danckwerts, Michael Paul; van Vuuren, Sandy (Planta Medica, 2021)
Acne is a skin condition arising from excess sebum production and microbial overgrowth within the pilosebaceous unit. Several commercial essential oils have shown promising activity against acne-related pathogens. Due to their volatility and thermal instability, the formulation of essential oils into commercial products remains a pharmaceutical challenge. Thus, this study aimed to develop a viable anti-acne topical treatment as an oil-in-water emulsified lotion to overcome these challenges. Chrysopogon zizanioides (vetiver) displayed noteworthy antimicrobial activity with a mean minimum inhibitory concentration of 0.14 mg/mL against Cutibacterium acnes, Staphylococcus aureus, Staphylococcus epidermidis, and Streptococcus pyogenes. Emulsified lotions containing C. zizanioides were developed through the hydrophilic-lipophilic balance approach. At tested hydrophilic-lipophilic balance values of 8, 9, and 10, C. zizanioides emulsified lotions displayed maximum stability at hydrophilic-lipophilic balance 9 with a minimum change in mean droplet size and polydispersity index of 20.61 and 33.33%, respectively, over 84 days. The C. zizanioides emulsified lotion at optimum hydrophilic-lipophilic balance 9 completely inhibited the growth of C. acnes and killed S. aureus, S. epidermidis, and S. pyogenes within 24 h. Additionally, the lotion retained antimicrobial activity against these test micro-organisms over the 84-day stability test period. Thus, the C. zizanioides emulsified lotion demonstrated physical stability and antimicrobial efficiency, making it an ideal natural product anti-acne treatment.
Keywords: acne; essential oil; Vetiveria zizanioides; HLB; emulsion; stability